2016
DOI: 10.1021/jacs.6b04446
|View full text |Cite
|
Sign up to set email alerts
|

Direct C–C Coupling of CO2 and the Methyl Group from CH4 Activation through Facile Insertion of CO2 into Zn–CH3 σ-Bond

Abstract: Conversion of CO2 and CH4 to value-added products will contribute to alleviating the green-house gas effect but is a challenge both scientifically and practically. Stabilization of the methyl group through CH4 activation and facile CO2 insertion ensure the realization of C-C coupling. In the present study, we demonstrate the ready C-C coupling reaction on a Zn-doped ceria catalyst. The detailed mechanism of this direct C-C coupling reaction was examined based on the results from density functional theory calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
128
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 65 publications
3
128
2
Order By: Relevance
“…Recently, Ge and co‐workers investigated the direct C−C coupling of CO 2 and CH 4 to form acetic acid on a Zn‐doped ceria catalyst by density functional theory (DFT) modeling;1 this is an attractive route as the direct conversion of CO 2 and CH 4 into acetic acid is a reaction with 100 % atom economy [Equation (1)]. However, this reaction is thermodynamically unfavorable under practical conditions.…”
mentioning
confidence: 99%
“…Recently, Ge and co‐workers investigated the direct C−C coupling of CO 2 and CH 4 to form acetic acid on a Zn‐doped ceria catalyst by density functional theory (DFT) modeling;1 this is an attractive route as the direct conversion of CO 2 and CH 4 into acetic acid is a reaction with 100 % atom economy [Equation (1)]. However, this reaction is thermodynamically unfavorable under practical conditions.…”
mentioning
confidence: 99%
“…The co-conversion of methane and carbon dioxide to valueadded chemicals represents an important subject in C 1 chemistry from energy and environmental perspectives, [1] but it is very difficult because of the inherent stability of both CH 4 and CO 2 .D ry reforming of methane (DRM) with CO 2 has been developed for generation of syngas (CO + H 2 ) [2] that can be converted to desired products by either alcohols synthesis or Fischer-Tropsch processes. [3] However,s uch indirect route is highly energy intensive.T he design of catalysts that can achieve the direct co-conversion of CH 4 and CO 2 thus becomes appealing driven by the economical consideration. [4] There have been several attempts at direct production of chemicals from CH 4 and CO 2 using heterogeneous catalysts including Cu/Co metal oxides, [5] oxide-supported noble metals (Rh, Pd, and Pt), [6] and metal-exchanged zeolites.…”
mentioning
confidence: 99%
“…[3] However,s uch indirect route is highly energy intensive.T he design of catalysts that can achieve the direct co-conversion of CH 4 and CO 2 thus becomes appealing driven by the economical consideration. [4] There have been several attempts at direct production of chemicals from CH 4 and CO 2 using heterogeneous catalysts including Cu/Co metal oxides, [5] oxide-supported noble metals (Rh, Pd, and Pt), [6] and metal-exchanged zeolites. [7] These direct processes still suffer from high temperature (> 700 K) or poor selectivity and low yield.…”
mentioning
confidence: 99%
“…Zn-doped ceriaw as found to be av ery efficient catalyst in activating the CÀHb ond of methanei nt he presence of CO 2 to form the CÀCc ouplingp roduct acetic acid. [206] Here the Zn sites stabilized the ÀCH 3 moiety through the formationo fa ZnÀCb ond, whereas ceria activated the CO 2 molecules and thus CÀCc oupling proceeded smoothly.I nav ery recent article Park et al reported the synthesis of acetic acid by simultaneous co-activation of CH 4 and CO 2 over Cu-loaded Li/Na/K/Ca-ZSM-5 materials [207] in am icro-reactor at 425-525 8Cw ith slow feeding of these gas mixtures. Here the Cu NPs facilitates the CÀHa ctivation, whereas the alkali anda lkaline earth metal sites promote the activation of CO 2 molecules so that the CÀC bond formation reactionoccurs, leading to the selectiveformation of CH 3 CO 2 H. Chen et al have also reportedt he synthesis of ethanol (C 2 H 5 OH)bypassing CO 2 into an aqueous dispersion of bimetallico xysulfides of Cu/Ni, Cu/Co,a nd Cu/Sn as heterogeneous catalyst under ambient conditions.…”
Section: Catalytic Sites and Mechanistic Aspects Of Co 2 Fixation Reamentioning
confidence: 98%
“…Zn‐doped ceria was found to be a very efficient catalyst in activating the C−H bond of methane in the presence of CO 2 to form the C−C coupling product acetic acid . Here the Zn sites stabilized the −CH 3 moiety through the formation of a Zn−C bond, whereas ceria activated the CO 2 molecules and thus C−C coupling proceeded smoothly.…”
Section: Catalytic Sites and Mechanistic Aspects Of Co2 Fixation Reacmentioning
confidence: 99%